Transformation of Approaches to Assessing the Investment Potential and Investment Attractiveness of Russian Regions - M. Yu. Elsukov; A. P. Isaev (Управленческое консультирование)
The issues of developing ideas about approaches to assessing the investment potential and investment attractiveness of Russian regions are considered. The characteristics of the reasons for the emergence of interest in studying the topic of investment attractiveness are given. The identification of stages in the development of research and changes in approaches to assessment is justified. The advantages and disadvantages of the traditional approach to the study of investment potential as a component of investment attractiveness are analyzed. The relevance of applying the approach to studying investment potential is substantiated from the standpoint of assessing the completeness of its use to ensure socioeconomic development.